Preparation of 4-Halobenzoate-Containing Phosphane-Based Building Blocks for Labeling Reactions Using the Traceless Staudinger Ligation - Mamat, Constantin; Köckerling, Martin (Synthesis, 2015)
Functionalized phosphane-containing key building blocks were synthesized that are suitable for the labeling of biologically active molecules by the traceless Staudinger ligation. Thus, a 2-(diphenylphosphanyl)phenyl 4-stannylbenzoate building block was converted into the 4-iodobenzoate by the introduction of iodine. The traceless Staudinger ligation was used to introduce the resulting 4-iodobenzoate moiety into selected molecules of pharmacological interest. Furthermore, the labeling procedure was used to insert the 4-iodobenzoate moiety into a peptide on solid support. Finally, a convenient recovery procedure of the key phosphane building block 2-(diphenylphosphanyl)phenol from 2-(diphenylphosphoryl)phenol was evaluated.
Keywords: conjugation; bioorthogonal; iodobenzoylation; recovery; labeling